2019
DOI: 10.1038/s41598-019-49550-x
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH overexpression in head and neck cancer: potential target for novel anticancer therapy

Abstract: The nine identified human homologues of E. coli AlkB 2-oxoglutarate (2OG) and Fe(II)-dependent dioxygenase, ALKBH1-8 and FTO, display different substrate specificities and diverse biological functions. Here we discovered the combined overexpression of members of the ALKBH family in head and neck squamous cell carcinomas (HNSCC). We found direct correlation of ALKBH3 and FTO expression with primary HNSCC tumor size. We observed unidentified thus far cytoplasmic localization of ALKBH2 and 5 in HNSCC, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 53 publications
3
52
0
1
Order By: Relevance
“…It associates with the activating signal cointegrator 1 complex subunit 3 of activating signal cointegrator complex thus being involved in the generation of ssDNA, to maintain genomic integrity . As in the case of ALKBH2, ALKBH3 is also overexpressed in different cancers, for example, rectal carcinoma, pancreatic cancer, head and neck squamous cell carcinoma (HNSCC), and others . The aforementioned information, with findings that knockdown of the ALKBH3 gene leads to a decrease in the diameter of tumor in mice, strongly suggest that ALKBH3 repair activity is necessary for tumor maintenance …”
Section: Impact Of Alkbh Proteins On Biological Processes In Higher Ementioning
confidence: 99%
See 3 more Smart Citations
“…It associates with the activating signal cointegrator 1 complex subunit 3 of activating signal cointegrator complex thus being involved in the generation of ssDNA, to maintain genomic integrity . As in the case of ALKBH2, ALKBH3 is also overexpressed in different cancers, for example, rectal carcinoma, pancreatic cancer, head and neck squamous cell carcinoma (HNSCC), and others . The aforementioned information, with findings that knockdown of the ALKBH3 gene leads to a decrease in the diameter of tumor in mice, strongly suggest that ALKBH3 repair activity is necessary for tumor maintenance …”
Section: Impact Of Alkbh Proteins On Biological Processes In Higher Ementioning
confidence: 99%
“…Additionally, ALKBH2 shows an important role in maintaining the rDNA gene integrity and transcription . It is worth mentioning that ALKBH2 promotes cancer development …”
Section: Impact Of Alkbh Proteins On Biological Processes In Higher Ementioning
confidence: 99%
See 2 more Smart Citations
“…Studies in mice model indicate that there is a positive correlation between the expression of FTO protein and body weight 7 . It has been suggested that FTO may directly regulate food intake, fat development, energy metabolism, cell proliferation, and cancer development [30][31][32][33][34][35][36][37][38] . It has also been found that the availability of glucose and amino acids regulates FTO protein expression: glucose/amino acid starvation leads to a decrease in the level of FTO protein 39 .…”
mentioning
confidence: 99%